2020
DOI: 10.1097/md.0000000000023664
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of fall incidence and risk factors in elderly patients after total joint arthroplasty

Abstract: Background: Falls in the elderly have become a serious social problem worldwide. Approximately a third of persons fall at least once in the year after total joint arthroplasty (TJA), but preventing and treating falls is still challenging in clinical practice. Until now, no formal systematic review or meta-analysis was performed to summarize the risk factors of falls after TJA. The present study aimed to quantitatively and comprehensively conclude the risk factors of falls after TJA in elderly pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 58 publications
1
20
0
1
Order By: Relevance
“…Our results suggested that approximately 40% of individuals with severe knee osteoarthritis fell at least once in the year before surgery, which is consistent with previous data (23% to 63%) 8 . The registered fall incidence was 13% and 23% at 6 and 12 months after surgery, also within the range of previous reports (13% to 42%) 8 , 11 . The differences across studies may be related to multiple factors, including methods for data collection, patient sources, diverse time points for assessment or even the inclusion of fall prevention strategies in the recovery processes.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results suggested that approximately 40% of individuals with severe knee osteoarthritis fell at least once in the year before surgery, which is consistent with previous data (23% to 63%) 8 . The registered fall incidence was 13% and 23% at 6 and 12 months after surgery, also within the range of previous reports (13% to 42%) 8 , 11 . The differences across studies may be related to multiple factors, including methods for data collection, patient sources, diverse time points for assessment or even the inclusion of fall prevention strategies in the recovery processes.…”
Section: Discussionsupporting
confidence: 90%
“…In the end-stages of the condition, the solution of choice is known as total knee replacement (TKR), a cost-effective procedure that alleviates the effects of potential fall contributors. It also decreases fall prevalence figures, reported to be between 13 and 42% at six months to one year after surgery 8 , 11 . However, a high proportion of patients present residual deficits, and preoperative risk factors are not always resolved 12 .…”
Section: Introductionmentioning
confidence: 65%
“…Another key benefit to the HIIT regime employed in this study is that no facilities or equipment are required, removing two further barriers (access to facilities and reticence to exercise in public [ 23 , 55 , 56 ]) to exercise for older adults. In addition, our HIIT protocol only included three exercises, addressing concerns about complexity [ 49 ], each of which are easily adaptable for those with, for example, joint restrictions which commonly occur in older age [ 57 ]. It is our belief, that in a pragmatic roll-out of equipment-free, unsupervised HIIT to improve the health of older adults, any exercise which can be performed safely to raise heart to > 85% of age-predicted maximum could be substituted into the temporal regime reported herein.…”
Section: Discussionmentioning
confidence: 99%
“…Проблема падения пациентов после эндопротезирования крупных суставов нижней конечности уже была освещена в нескольких обзорах. В течение года после эндопротезирования тазобедренного сустава приблизительно треть всех пациентов переживают по крайней мере один эпизод падения, при этом госпитальные случаи составляют всего 1 % [50,51]. Стоит отметить, что в этих аналитических материалах наиболее значимыми факторами риска падения пожилых пациентов после эндопротезирования крупных суставов нижних конечностей названы анамнестические данные о падении до операции, симптомы депрессии, ТЭТС по сравнению с ТЭКС, избыточная масса тела, заболевания сердца и лёгких [50, 51,…”
Section: Discussionunclassified